2013
DOI: 10.1364/ao.52.005083
|View full text |Cite
|
Sign up to set email alerts
|

Talbot effect of quasi-periodic grating

Abstract: Theoretic and experimental studies of the Talbot effect of quasi-periodic gratings are performed in this paper. The diffractions of periodic and quasi-periodic square aperture arrays in Fresnel fields are analyzed according to the scalar diffraction theory. The expressions of the diffraction intensities of two types of quasi-periodic gratings are deduced. Talbot images of the quasi-periodic gratings are predicted to appear at multiple certain distances. The quasi-periodic square aperture arrays are produced wi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
4
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 18 publications
(4 citation statements)
references
References 21 publications
0
4
0
Order By: Relevance
“…The wavefront sensor based on the Talbot effect was recently considered as the alternative to the Shack-Hartmann sensor [15,16]. It was confirmed that replacement of the lenslet array by the diffraction grating eliminates some limitations of the Shack-Hartmann sensor due to greater flexibility of the device.…”
Section: Introductionmentioning
confidence: 98%
“…The wavefront sensor based on the Talbot effect was recently considered as the alternative to the Shack-Hartmann sensor [15,16]. It was confirmed that replacement of the lenslet array by the diffraction grating eliminates some limitations of the Shack-Hartmann sensor due to greater flexibility of the device.…”
Section: Introductionmentioning
confidence: 98%
“…In order to further develop the potential of this phenomenon, quasi-periodic and superimposed diffraction gratings are proposed to use. [26,27] The latter can be synthesized by the modulation superposition method. [28,29] The use of superimposed gratings expands the possibilities for configuring the spatial distributions of the light field, which can be used in photonics, nonlinear and quantum optics, atomic and laser physics.…”
Section: Introductionmentioning
confidence: 99%
“…This work proposes to transfer the concept of self-imaging to lateral-aperiodic objects [27,28] and mainly investigates the Talbot effects for Fibonacci geometry. Considering that the Talbot effects are distinct only in the paraxial approximation and when the illuminated geometry tends to infinity, this work introduces the cut-and-projection construction techniques [14,29], which capture the entire infinite Fibonacci structure in a single two-dimensional computational cell.…”
Section: Introductionmentioning
confidence: 99%